Tree of Science - ToS: A Web-Based Tool for Scientific Literature Recommendation. Search Less, Research More! - Martha Zuluaga; Sebastian Robledo; Oscar Arbelaez-Echeverri; German A. Osorio-Zuluaga; Nestor Duque-Méndez (Issues in Science and Technology Librarianship)
Tree of Science (ToS) is an integrated web-based platform for a comprehensive analysis of scientific literature. ToS is designed to facilitate finding relevant literature and can be used by students, researchers, and academics. Based on graph theory metrics, this tool visualizes the works in a knowledge field as a tree where the roots are classic articles, the trunk represents those articles that allow the area to grow, and the leaves are the recently published articles. This article provides a description of how to search, format, and upload the data and identify significant literature in a specific research area. Finally, a brief description of how the Tree of Science works.